Agaricus brunneosporus, a new species from Punjab, Pakistan (Bangladesh Journal of Plant Taxonomy, 2025)
Agaricus species are ecologically and economically significant, yet their diversity in underexplored regions like Pakistan remains poorly documented. This study investigated Agaricus species from Bahawalnagar district, Punjab, Pakistan. Specimens were collected from different locations in Bahawalnagar, followed by morphological examination based on macroscopic and microscopic features. For molecular identification, DNA was extracted, and the ITS region of the nrDNA was sequenced. Phylogenetic analysis was conducted using Maximum Likelihood methods to determine the taxonomic placement of the species under investigation. The newly discovered species is morphologically similar to A. dunensis, with a brownish-orange central disk and light brown squamules becoming sparser at the margins. Basidiospores were subglobose to broadly ellipsoid, measuring 3.9–4.8 × 3.1–4.1 μm, and the species displayed clavate to narrowly clavate cheilocystidia. Phylogenetic analysis of the ITS region confirmed the distinctiveness of this species within Agaricus sect. Minores. The findings highlight the diversity of macrofungi in this region, with this species representing a previously undocumented taxon. This discovery enhances knowledge of Pakistan's fungal diversity and emphasizes the importance of exploring understudied regions.Bangladesh J. Plant Taxon. 32(1): 83-92, 2025 (June)